Wytrzymałość pływacka i biegowa studentów kierunku wychowanie fizyczne na podstawie testu Coopera = Endurance swimming and gear students of physical education based on the basis of the Cooper's test - Banach, Jan; Cieślicka, Mirosława; Muszkieta, Radosław; Zukow, Walery; Stępniak, Robert (Journal of Education, Health and Sport, 2015)
Banach Jan, Cieślicka Mirosława, Muszkieta Radosław, Zukow Walery, Stępniak Robert. Wytrzymałość pływacka i biegowa studentów kierunku wychowanie fizyczne na podstawie testu Coopera = Endurance swimming and gear students of physical education based on the basis of the Cooper's test. Journal of Education, Health and Sport. 2015;5(5):445-462. ISSN 2391-8306. DOI 10.5281/zenodo.18157 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A445-462 https://pbn.nauka.gov.pl/works/562614 http://dx.doi.org/10.5281/zenodo.18157 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2015. Revised 18.04.2015. Accepted: 24.05.2015. Wytrzymałość pływacka i biegowa studentów kierunku wychowanie fizyczne na podstawie testu Coopera Endurance swimming and gear students of physical education based on the basis of the Cooper's test Jan Banach, Mirosława Cieślicka, Radosław Muszkieta, Walery Zukow, Robert Stępniak IKF, WKFZIT, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Wytrzymałość i wydolność można badać różnymi metodami. Na kierunku wychowania fizycznego Uniwersytety Kazimierza Wielkiego podjęto badania metodą biegowego i pływackiego testu Coopera. Do badań na sali gimnastycznej i na pływalni przystąpiło i ukończyło 59 studentów. Dokonano analizy wyników z podziałem na wyniki kobiet i mężczyzn z wyróżnieniem studentów uprawiających czynnie wybrane dyscypliny sportu. Wynikiem pracy jest stwierdzenie że przebadani studenci posiadają w znakomitej większość bardzo dobrą i dobrą wytrzymałość. Nie stwierdzono aby studenci czynnie uprawiający wybrane dyscypliny sportowe wyróżniali się wyższą wytrzymałością. Słowa kluczowe: pływanie, Test pływacki, Test Coopera, wytrzymałość. Abstract Endurance performance can be investigated by different methods. At the direction of physical education Universities Casimir the Great been investigated by cross-country skiing and swimming Cooper test. To study the gym and the swimming pool has acceded and graduated 59 students. The analysis of the results from the division of the results for men and women with honors students engaged actively chosen sport. The result of work is the finding that students have screened the vast majority of very good and good strength. There were no students to actively cultivating selected sports disciplines distinguished by a higher resistance. Keywords: swimming, pool Test, Test Cooper endurance.